Development of a CRISPR/Cas9 system for high efficiency multiplexed gene deletion in Rhodosporidium toruloides. Issue 8 (21st May 2019) - Schultz, J. Carl; Cao, Mingfeng; Zhao, Huimin
Abstract: The oleaginous yeast Rhodosporidium toruloides is considered a promising candidate for production of chemicals and biofuels thanks to its ability to grow on lignocellulosic biomass, and its high production of lipids and carotenoids. However, efforts to engineer this organism are hindered by a lack of suitable genetic tools. Here we report the development of a CRISPR/Cas9 system for genome editing in R. toruloides based on a fusion 5S rRNA–tRNA promoter for guide RNA (gRNA) expression, capable of greater than 95% gene knockout for various genetic targets. Additionally, multiplexed double‐gene knockout mutants were obtained using this method with an efficiency of 78%. This tool can be used to accelerate future metabolic engineering work in this yeast. Abstract : A highly efficient CRISPR/Cas9 gene editing system was developed in the oleaginous yeast Rhodosporidium toruloides . By tuning Cas9 expression and developing a novel 5S rRNA‐tRNA promoter for gRNA expression, Schultz and coworkers demonstrated a single‐gene knockout of the carotenogenic reporter gene CRTYB with greater than 99% efficiency, and multiplexed deletion of CRTYB and LEU2 with 78% combined efficiency.